1994
DOI: 10.1128/iai.62.5.1920-1926.1994
|View full text |Cite
|
Sign up to set email alerts
|

Protection of C3H/HeN mice from challenge with Borrelia burgdorferi through active immunization with OspA, OspB, or OspC, but not with OspD or the 83-kilodalton antigen

Abstract: Recent advances in the development of animal models for Lyme borreliosis have provided means of identifying potential targets for the design of a subunit vaccine to prevent this disease. The C3H/HeN mouse model was used to study several Borrelia burgdorfieri antigens from a single isolate for their ability to elicit borreliacidal and protective antibodies. The ospA, ospB, ospC, ospD, and 83-kDa genes from a California isolate, SON 188, were cloned and expressed in Escherichia coli as proteins fused to the C-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 46 publications
1
85
2
Order By: Relevance
“…This observation and the inability of OspA vaccination to sustain high-levels of anti-OspA borreliacidal antibodies [32], increased e¡orts to evaluate the ability of OspC to provide protection against infection with B. burgdorferi. However, anti-OspC borreliacidal antibodies were not detected in immune serum [12,28,29]. A progressive investigation demonstrated that borreliacidal antibodies against recombinant OspC antigen could be detected in sera from patients with early Lyme borreliosis, and that the detection of borreliacidal activity was dependent on the presence of high levels of OspC on the surface of B. burgdorferi [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation and the inability of OspA vaccination to sustain high-levels of anti-OspA borreliacidal antibodies [32], increased e¡orts to evaluate the ability of OspC to provide protection against infection with B. burgdorferi. However, anti-OspC borreliacidal antibodies were not detected in immune serum [12,28,29]. A progressive investigation demonstrated that borreliacidal antibodies against recombinant OspC antigen could be detected in sera from patients with early Lyme borreliosis, and that the detection of borreliacidal activity was dependent on the presence of high levels of OspC on the surface of B. burgdorferi [24].…”
Section: Discussionmentioning
confidence: 99%
“…Titration of borreliacidal activity was performed as described by Probert and LeFebvre [12], and Ma and Coughhlin [27], with slight modi¢cations. Brie£y, three species of Borrelia were incubated in BSK II medium and the concentrations adjusted to 1U10 6 cells ml 31 by adding fresh medium.…”
Section: Borreliacidal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In our current study, despite a rigorous humoral immune response against NDV, these mice failed to develop a robust serum antibody response against tested NDV-expressed borrelial antigens. The fact that bacterially expressed forms of OspC and BmpA are immunogenic in C3H mice [36,40,42], it raises the possibility that the near absence of a murine humoral immune response to borrelial proteins expressed by NDV vectors may be influenced by the production of glycosylated forms of these proteins by NDV. It is known that glycans can protect some viral glycopeptides from degradation in the endocytic compartments of antigen presenting cells [58].…”
Section: Discussionmentioning
confidence: 99%
“…Robust antibody responses against both antigens are detectable in infected hosts including humans that are useful for serodiagnosis of Lyme disease [38,39]. In addition, while OspC immunization results in generation of strain-specific immunity [40][41][42], BmpA immunization interferes with B. burgdorferi persistence in a tissue-specific manner, only in the joints [36]. Although the vaccine potential of either antigen is somewhat limited, OspC and BmpA were selected in our study due to their well-known immunogenicity.…”
Section: Introductionmentioning
confidence: 99%